Dynamics of Rotating Spin-Orbit-Coupled Spin-1 Bose-Einstein Condensates With In-Plane Gradient Magnetic Field in an Anharmonic Trap - Yang, Hui; Zhang , Qing; Jian , Zaihe (Frontiers in Physics, 2022)
We investigate the dynamics of rotating spin-orbit-coupled spin-1 Bose-Einstein condensates (BECs) in an in-plane gradient magnetic field, which is confined in an anharmonic trap. In the case of rotating spin-orbit-coupled spin-1 BECs with given parameters, the system evolves from initial disk-shaped condensates into drastic turbulent oscillations and ghost vortices on the surface of the component densities due to the surface wave excitations, and then into two final vortex necklaces along the azimuthal direction with a irregular density hole, in which the vortices differ by one quantum number in turn. For the case of rotating spin-orbit-coupled spin-1 BECs with in-plane gradient magnetic field, with the dynamic evolution, the system undergoes a transition from an initial central polar-core vortex to violent turbulent oscillations and then to a final vortex chain along the diagonal of BECs, with the remaining vortices symmetrically distributed on both sides in individual component. In addition, the corresponding spin texture undergoes a transition from plane wave phase to double half-antiskyrmion necklaces for the former case, and a transition from a structure similar to a quadrupole magnetic field to a half-antiskyrmion chain, with the rest of half-antiskyrmions on both sides. During the dynamic evolution process, the angular momentum increases gradually, and then approaches to a convergent value.